Ta'lim Al-'Arabiyyah 'Ala Dhau’ An-Namudzaj Al-Haramiyyah - Zulhannan Zulhannan; Umi Musyarrofah (Institut Agama Islam Negeri (IAIN) Metro, 2019)
This article says on the Arabic teaching and pyramid model. The first is consists of Arabic definition, its contents, and its characteristics. The second is comprised of pyramid model definition, its teaching steps, and its matter sample. From the data, so the research finding is Arabic base on the pyramid model. وهذه الكتابة تبحث عن تعليم العربية والنموذج الهرمية.فالأولي: تتكون من مفهوم العربية؛ وموادها؛ وخصائصها. والثانية: تحتوي على مفهوم النموذج الهرمية؛ وخطوات تدريسها؛ وأمثلة موادها. ومن هذه البيانات، فاكتشاف البحث هو العربية على ضوء النموذج الهرمية.